NuSTAR detection of 4s Hard X-ray Lags from the Accreting Pulsar GS 0834-430 - Bachetti Matteo; Miyasaka Hiromasa; Harrison Fiona; Fürst Felix; Barret Didier; Bellm Eric C.; Boggs Steven E.; Chakrabarty Deepto; Chenevez Jerome; Christensen Finn E.; Craig William W.; Grefenstette Brian W.; et al. (EPJ Web of Conferences, 2014)
The NuSTAR hard X-ray telescope observed the transient Be/X-ray binary GS 0834–430 during its 2012 outburst. The source is detected between 3 – 79 keV with high statistical significance, and we were able to perform very accurate spectral and timing analysis. The phase-averaged spectrum is consistent with that observed in many other magnetized accreting pulsars. We fail to detect cyclotron resonance scattering features in either phase-averaged nor phase-resolved spectra that would allow us to constrain the pulsar’s magnetic field. We detect a pulse period of ~ 12:29 s in all energy bands. The pulse profile can be modeled with a double Gaussian and shows a strong and smooth hard lag of up to 0.3 cycles in phase, or about 4s between the pulse at ~ 3 and ≳ 30 keV. This is the first report of such a strong lag in high-mass X-ray binary (HMXB) pulsars. Previously reported lags have been significantly smaller in phase and restricted to low-energies (E<10 keV). We investigate the possible mechanisms that might produce such lags. We find the most likely explanation for this effect to be a complex beam geometry.